Halfspace modeling of elastic-plastic contact of rough surfaces - Hauer, Franz; Willner, Kai (COMPLAS XI, 2011)
Friction has a significant influence on the tool lifetime and the quality of products in manufacturing processes. Real surfaces are always rough, so that for moderate loads contact occurs only at surface roughness peaks. Thus the real contact area A real is smaller than the apparent contact area A 0. Adhesive forces, which are an important contribution to friction, can only be transferred within A real. Consequently A real has to be determined in order to analyse the tribological behaviour of technical surfaces. The halfspace approach is used because of its advantage in numerical effort compared to the Finite-Element-Method. Due to the fact that contact pressures can be very large the plastic deformation of roughness peaks has to be taken into account. Therefore a three-dimensional plasticity algorithm is implemented into the halfspace model.
UnivIS-Import:2015-04-16:Pub.2011.tech.FT.FT-TM.halfsp_9
Keywords: Computational plasticity; Contact; Halfspace; Metal forming